Implementasi High Availability AWS pada Situs Web Berbasis Framework CodeIgniter - Akrim Teguh Suseno; Indra Kurniawan; Mohammad Reza Maulana (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study focuses on designing and implementing a High Availability (HA) architecture for a web application built with CodeIgniter using Amazon Web Services (AWS). The objective is to enhance system reliability while minimizing downtime. A prototype-based research method is applied, allowing iterative development, testing, and evaluation of the system. The proposed architecture utilizes an Application Load Balancer (ALB) to distribute incoming traffic efficiently, multiple Amazon EC2 instances deployed across different Availability Zones for redundancy, and Amazon RDS with replication to ensure database reliability and consistency. Performance testing includes both load testing and failure simulation scenarios. The results indicate that the system achieves an average response time between 120 and 180 milliseconds under normal conditions and remains stable when handling concurrent users. During failure testing, the system successfully performs failover in under 10 seconds without noticeable service disruption. Additionally, database replication maintains data integrity with no detected data loss, confirming improved availability, scalability, and reliability.